Challenges and Opportunities Management Human Resources in Industry 4.0 Focuses on Digital Skills Syamsudinnoor International Banjarmasin Airpot, South Kalimantan - Firdaus, Firdaus; Ambarwati, Riris (International Journal of Economics (IJEC), 2024)
The Industrial Era 4.0 has brought profound changes in various industrial sectors throughout the world. This research explores the challenges and opportunities of human resource management (HR) in facing these changes, with a focus on Syamsudin Noor International Airport, Banjarmasin, South Kalimantan. The digital era and Industry 4.0 have changed the business landscape, demanding rapid adaptation in managing the workforce. A key challenge is the lack of digital skills required by employees to operate in an increasingly digitalized environment. This research provides an overview of changes at Syamsudin Noor Airport, which has an important role as a regional gateway and logistics center. The airport is facing changes in technology, regulations and increasing customer expectations. HR management must play a strategic role in overcoming this challenge. The conclusion of this research is that HR management must prioritize developing employee digital skills, changing organizational culture, and understanding regulations related to the digital era. This is crucial to ensure the success of Syamsudin Noor Airport and similar organizations in facing Industry 4.0. Opportunities exist in operational efficiency, data analytics and work flexibility. In conclusion, adaptive HR management and a focus on developing digital skills will play a key role in responding to challenges and exploiting opportunities in the Industry 4.0 era.